Integrating Computational Thinking and Empowering Metacognitive Awareness in Stem Education - Markandan, Nagalaxmy; Osman, Kamisah; Halim, Lilia (Frontiers in Psychology, 2022)
Education digitization highly enthuses learners for deeper learning and developing thought processes in formulating problems and their solution effectively in their real-life circumstances. Implementing computational thinking skills through programming in Malaysian primary and secondary school STEM curriculum create huge challenges especially among STEM educators. This study highlights the integration of four major theories in developing the Metacognitive Empowerment by Computational Thinking (ME-CoT) learning module by cultivating computational thinking through programming skill to promote metacognitive awareness in Biology students. Pilot research was conducted to investigate the reliability of ME-CoT learning module. Since the study sample was less than 30 students then, the consistency of the measurements, Pearson’s r was calculated to identify stability reliability. Finding revealed that, ME-CoT learning module has a very strong stability reliability with a value of r=0.974 and provides advantages such as assisting students to understand the STEM lesson meaningfully.